The Reconfiguration of Digital Piety in Aceh: A Case Study of Teungku Inong on Instagram - Putri Maulina; Irwan Abdullah; Wiwik Sushartami; Arifah Rahmawati (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2026)
This article examines how teungku inong—female Islamic educators and leaders in Aceh—use Instagram to mediate religious authority and piety within a historically male-dominated religious field. Employing a qualitative interpretive approach, the study draws on visual discourse analysis of selected Instagram posts from three teungku inong, focusing on visual composition, bodily comportment, spatial arrangement, and accompanying captions. The analysis is grounded in scholarship on digital religion, pious agency, and mediatization, particularly concepts of embodied piety, mediated authority, and critical but compliant agency. The findings demonstrate that Instagram does not generate new religious authority but operates as a mediating infrastructure that extends, archives, and amplifies authority already established offline. Epistemic authority is visualised through academic conferences, majelis taklim, and public forums; genealogical and institutional legitimacy is reinforced through references to sanad, proximity to senior ulama, and participation in formal religious bodies; while social engagement—such as environmental initiatives and women’s advocacy—functions as an extension of embodied moral discipline into the public sphere. Conceptually, the article argues that digital piety in this context is best understood as continuity and reconfiguration rather than rupture. Instagram translates embodied and relational practices into visible, repeatable, and networked forms, enabling teungku inong to consolidate religious authority across offline and online domains while remaining grounded in established religious norms.